Uptake of micropollutant-bisphenol A, methylene blue and neutral red onto a novel bagasse-β-cyclodextrin polymer by adsorption process. (November 2020) - Mpatani, Farid Mzee; Aryee, Aaron Albert; Kani, Alexander Nti; Guo, Qiehui; Dovi, Evans; Qu, Lingbo; Li, Zhaohui; Han, Runping
Abstract: The presence of emerging micropollutants and dyes in water resource has raised global concern about their intense effects to aquatic environments, ecosystem and human health in general. So far, various adsorbents have been suggested for reducing the levels of bisphenol A, methylene blue and neutral red contamination in wastewaters. However, a number of these adsorbents seemed to have low adsorptive capacities and regeneration performances. In view of these, batch experiment was performed to decontaminate these pollutants from aqueous solutions using an optimized bagasse-β-cyclodextrin polymer (SB-β-CD). Characterization studies of SB-β-CD were performed using FTIR, pH point of zero charge, XRD and BET methods. Adsorption of BPA, MB and NR was favored at lower temperature (298 K) and pH of 7.0, 9.0 and 6.0, respectively. The maximum adsorption capacity of BPA, MB and NR at 298 K was 121, 963 and 685 mg g −1, respectively. Hydrogen bonding through host-guest inclusion and electrostatic interactions could respectively attribute to uptake of BPA and MB/NR onto SB-β-CD. Adsorption kinetics of three pollutants followed pseudo-second-order model. Langmuir and Freundlich models were fitted to describe the adsorption of BPA and MB/NR, respectively. Thermodynamic parameters confirmed the occurrence of physical adsorption which is spontaneous and exothermic in nature. SB-β-CD loaded with BPA and MB/NR was certainly reused by 75% ethanol and 0.1 mol L −1 HCl solutions, respectively. Novel SB-β-CD showed better adsorptive capacity and regeneration performances; consequently can offers practical application for removal of BPA, MB and NR from wastewaters. Graphical abstract: Image 1 Highlights: Bagasse- β -cyclodextrin polymer was synthesized to remove BPA, MB and NR. Molar ratio, temperature and reaction time play major roles in produce SB- β -CD. Crosslinking of bagasse with β -CD increases adsorptive properties of bagasse. SB- β -CD exhibits excellent adsorption capacity and easy regeneration.